2018
DOI: 10.1097/hp.0000000000000904
|View full text |Cite
|
Sign up to set email alerts
|

Dose Estimation in Recycling of Decontamination Soil Resulting From The Fukushima NPS Accident For Road Embankments

Abstract: Since the Fukushima nuclear power station accident, large quantities of radiocesium-contaminated soil generated from decontamination activities have been stored in Fukushima prefecture. To complete the final disposal of decontamination soil, reducing the disposal volume through recycling can prove effective. The Ministry of the Environment of Japan has developed a policy of handling low-activity decontamination soil as recycled materials under the management of public authority. The recycling is limited to civ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…This result was confirmed by Yamashita et al (2014), who showed that 99 wild plants grown in paddy and upland fields had a very low phytoextraction efficiency. Tamaoki et al (2016) reached the same conclusions, although they suggested Kochia (Bassia scoparia) as a potential candidate for phytoremediation even though its efficiency in removing 137 Cs would require numerous cultivation rounds. Accordingly, given the low efficiency of phytoextraction, the main remediation strategy consists of removing the surface layer of soils with the majority of radiocesium.…”
Section: Soil and Farmland Decontamination And Soil To Plant Transfersmentioning
confidence: 69%
See 3 more Smart Citations
“…This result was confirmed by Yamashita et al (2014), who showed that 99 wild plants grown in paddy and upland fields had a very low phytoextraction efficiency. Tamaoki et al (2016) reached the same conclusions, although they suggested Kochia (Bassia scoparia) as a potential candidate for phytoremediation even though its efficiency in removing 137 Cs would require numerous cultivation rounds. Accordingly, given the low efficiency of phytoextraction, the main remediation strategy consists of removing the surface layer of soils with the majority of radiocesium.…”
Section: Soil and Farmland Decontamination And Soil To Plant Transfersmentioning
confidence: 69%
“…As 22 million m 3 of decontamination soil (i.e. 90 % of the total) and incineration ash waste (10 %) is expected to be produced through remediation of the fallout-impacted region, recycling may be instrumental for reducing this volume (Takai et al, 2018). The Japanese Ministry of Environment developed a policy to separate decontamination soil into low-and high-activity soils, the former being "recycled" in public projects.…”
Section: Soil Recyclingmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, owing to the strong and nearly irreversible bond of radiocesium to fine soil particles, the majority of FDNPP derived 137 Cs is stored within the topsoil (i.e. the top 5 cm) in undisturbed soils (Lepage et al, 2014;Matsunaga et al, 2013;Takahashi et al, 2015;Mishra et al, 2015;Matsuda et al, 2015). Mishra et al (2015) reported that for these undisturbed soils, the vertical migration of radiocesium down the soil profile was slower in forest soils compared to grassland soils.…”
Section: Strategies For Decontamination In Various Environments and mentioning
confidence: 99%